Finite Element Analysis of Stress Distribution During Retraction of Mandibular Incisors - Nada M Al-Sayagh; Mohammad N Mahmood; Rasha Y Al-Darzi (University of Mosul, College of Dentistry, 2013)
Aims: The present study aimed to determine stress and strain distribution on the four lower incisors under the effect of (400g) calculated retracted orthodontic force. Materials and methods: Using finite element analysis method, frictionless retraction technique was successfully used with the aid of continuous (delta loop) on NiTi, Stainless steel wires without gable bends and stainless steel looped wire using 40°. gable bends(20° alpha, 20° beta gable) respectively. Results: High compressive stress concentration in labiolingual direction are observed near the point of force application and along the line of action of orthodontic wire at the crown of both lateral and central incisors. Conclusions: The stress distribution is not the same for the all retracted segment and there was independent movement of lateral incisors from the central incisors except for the retraction using NiTi wires which exhibits uniform movements for both lateral and central incisors.